2017
DOI: 10.1080/2162402x.2017.1310358
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble programmed death protein 1 (sPD-1) and soluble programmed death ligand 1 (sPD-L1) in advanced pancreatic cancer

Abstract: Up to now, the efficacy of programmed death protein 1/programmed death ligand 1 (PD-1/PD-L1) blockade in pancreatic cancer (PC) remains uncertain. Serum levels of soluble PD-1 and PD-L1 (sPD-1/sPD-L1) have been reported to be independent prognostic factors in solid tumors susceptible to checkpoint blockade. Provenience, regulation and immunologic function of sPD-1 and sPD-L1 in cancer are poorly understood. To the best of our knowledge, sPD-1 and sPD-L1 have not been measured conjointly in any cancer type yet.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
115
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 39 publications
13
115
4
1
Order By: Relevance
“…20,21 Another possible approach for reversing vaccination failure is to combine sPD-1, which is a soluble form of PD-1 detected in the blood of patients with autoimmune disease (AID), associated with intense inflammation through blockade of the PD-1 suppressive pathway by interaction with PD-L1. 22,23 In the present study, we found that senescent whole-tumor-cell vaccination significantly shifted DC towards maturity followed by Tcell activation in vivo. Moreover, stress-induced senescent cells reengineered to secrete sPD-1 were safer and much more effective than control when vaccinated into mice.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…20,21 Another possible approach for reversing vaccination failure is to combine sPD-1, which is a soluble form of PD-1 detected in the blood of patients with autoimmune disease (AID), associated with intense inflammation through blockade of the PD-1 suppressive pathway by interaction with PD-L1. 22,23 In the present study, we found that senescent whole-tumor-cell vaccination significantly shifted DC towards maturity followed by Tcell activation in vivo. Moreover, stress-induced senescent cells reengineered to secrete sPD-1 were safer and much more effective than control when vaccinated into mice.…”
Section: Introductionsupporting
confidence: 52%
“…The clinical effect of blockade has been shown in a number of advanced malignancies . Another possible approach for reversing vaccination failure is to combine sPD‐1, which is a soluble form of PD‐1 detected in the blood of patients with autoimmune disease (AID), associated with intense inflammation through blockade of the PD‐1 suppressive pathway by interaction with PD‐L1 …”
Section: Introductionmentioning
confidence: 99%
“…PD‐L1 is mainly expressed in tumor cells; therefore, high concentrations of PD‐L1 represent large tumor volumes and/or highly malignant tumors . On the other hand, several reports have demonstrated no significant associations between tumoral PD‐L1 expression and serum PD‐L1 levels, suggestive of the fact that a high level of serum PD‐L1 might be related to the immunological condition of the patient. Similar to hepatocellular carcinoma and gastric cancer, no associations were noted between serum PD‐L1 levels and tumor stage or tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with EGFR‐mutated advanced NSCLC who were treated with erlotinib and had a more favorable outcome showed higher expression of sPD‐1 in their blood . In contrast, serum levels of sPD‐1 or sPD‐L1 had no effect (adverse or otherwise) on the overall survival of advanced pancreatic cancer patients, although these levels were indicative of systemic inflammation in pancreatic cancer …”
Section: Immune Checkpoint Molecules: Regulating the Immune Response mentioning
confidence: 99%